CD57 expression in CD8 T cells and development of cutaneous squamous cell carcinoma in renal transplant recipients: a prospective cohort study. (26th February 2015) - Bottomley, Matthew; Harden, Paul; Wood, Kathryn
Abstract: Background: Cutaneous squamous cell carcinoma is the most common malignancy in renal transplant recipients and a major cause of morbidity and mortality. Various measures have been proposed to identify recipients at increased risk of developing this cancer to allow targeted intervention. CD57 expression might represent a marker of T-cell exhaustion; we hypothesised that expression could predict development of squamous cell carcinoma in renal transplant recipients, and undertook a prospective cohort study to assess its predictive value. Methods: Renal transplant recipients with and without previous squamous cell carcinoma (matched by race, age, sex, and immunosuppression duration) were recruited at routine clinical follow-up. Peripheral blood lymphocytes were analysed by flow cytometry. Three previously developed risk scores (Harden, Urwin, and Harwood), based on clinical phenotype, were also evaluated. The outcome event was histologically diagnosed squamous cell carcinoma during the study. Ethics approval was granted by local committee. Hazard ratios (HR) were calculated by Cox regression. Findings: 57 renal transplant recipients with and 53 without previous squamous cell carcinoma were recruited. During a median follow-up of 309 days (IQR 223–409), 20 recipients developed this cancer (including four with a first diagnosis). On univariate analysis increasing age at enrolment, previous squamous cell carcinoma, having the CD57hi phenotype (≥50% of CD8 T cells expressing CD57), and increasing clinical risk score were predictive of cancer development. However, all three clinical risk scores were no longer predictive when adjusted for age. By contrast, transplant recipients displaying CD57hi were at significantly increased risk of future squamous cell carcinoma compared with CD57lo recipients (≤50% of CD8 T cells expressing CD57) (HR 5·0, 95%CI 1·11–22·3; p=0·04); risk remained significant after adjustment for both age (1·1, 1·0–1·1; p=0·04) and history of previous squamous cell carcinoma (3·5, 1·12–11·2; p=0·04). Interpretation: Our results show that the CD57hi phenotype is a stronger predictor of squamous cell carcinoma development in long-term, at-risk renal transplant recipients than previously identified clinical phenotypes. This finding could help in the identification of renal transplant recipients at high risk of this cancer, who would benefit from intensive dermatological screening and immunosuppression reduction. Funding: Wellcome Trust, Oxford University Hospitals Research Services Committee.